Budaya Ujian dan Krisis Evaluasi Humanis: Telaah Kritis atas Paradigma Evaluasi Kuantitatif dalam Perspektif Pedagogi Kritis Paulo Freire Dan Henry A. Giroux” - Eunike Agustina; Esa Tedja Manahanie; Glory Kriswantara (Sekolah Tinggi Teologi Bethel Ambon, 2026)
Assessment practices in Christian Religious Education (CRE) remain predominantly dominated by quantitative approaches that emphasize scores and measurable learning outcomes. Such approaches are insufficient to capture the holistic development of faith, character, and spiritual maturity, which constitute the primary goals of Christian education. This study aims to construct a humanistic paradigm of assessment in Christian Religious Education by integrating the theological foundations of Christian education with the critical pedagogical perspectives of Paulo Freire and Henry A. Giroux. The study employs a qualitative library research approach. Data were analyzed using a critical-constructive framework through the examination of Christian education literature, educational assessment theories, the Merdeka Curriculum, and the educational philosophies of Freire and Giroux. The findings indicate that assessment in Christian Religious Education should not be limited to measuring cognitive achievement but should function as a dialogical, reflective, and transformative process that fosters faith formation, character development, and social responsibility. Based on this synthesis, the study proposes a humanistic assessment model that positions assessment as a means of discipleship, liberation, and reconciliation, grounded in the Christian values of love, justice, and respect for human dignity as the Imago Dei. This model offers a conceptual framework for developing holistic, humanistic, and contextually relevant assessment practices in Christian Religious Education.